2017
DOI: 10.1039/c7dt02540h
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature transmetallation from tris(pentafluorophenyl)borane to cyclometallated iridium(iii)

Abstract: Transmetallation reactions involving organoboron reagents and transition metals are legion in synthetic organometallic chemistry and homogeneous catalysis. Triarylboranes (BAr) have been observed to participate in transmetallation reactions with many transition metals, typically following abstraction of an alkyl (R) or hydride ligand by the Lewis acidic borane. Here, an unusual transmetallation strategy is described where an aryl group from a borane replaces a weakly coordinated PF ligand. The precursors Ir(C^… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…General procedure for preparation of 1 b and 1 c : The complexes 1 b and 1 c were synthesized following the previously published method for 1 a by treating the Ir dimer [Ir(C^N) 2 (μ‐Cl)] 2 with 2,6‐dimethylphenyl isocyanide in CH 2 Cl 2 inside the glove box …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…General procedure for preparation of 1 b and 1 c : The complexes 1 b and 1 c were synthesized following the previously published method for 1 a by treating the Ir dimer [Ir(C^N) 2 (μ‐Cl)] 2 with 2,6‐dimethylphenyl isocyanide in CH 2 Cl 2 inside the glove box …”
Section: Methodsmentioning
confidence: 99%
“…The syntheses startw ith the complexes [Ir(C^N) 2 (CNAr dmp )Cl],w hich are easily prepared by treatingt he dimers [Ir(C^N)(m-Cl)] 2 with two equivalents CNAr dmp at room temperature;t he complex [Ir(F 2 ppy) 2 (CNAr dmp )Cl] (1a)w as reported previously and other related complexes have been prepared via an analogous route. [51,54] Our group has previously shown that am ore reactive Ir precursor [Ir(C^N) 2 (CNAr)(FPF 5 )] can be prepared by treating [Ir(C^N) 2 (CNAr)Cl] complexesw ith one equivalento f AgPF 6 ,r eplacing the chloride anion with aw eakly coordinated k 1 -PF 6 À anion. [51] In this way,t he [Ir(F 2 ppy) 2 (CNAr dmp )(FPF 5 )] precursor was prepared.…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 99%
See 3 more Smart Citations